Utilization and physical activity levels at renovated and unrenovated school playgrounds - Colabianchi, Natalie; Kinsella, Audrey E.; Coulton, Claudia J.; Moore, Shirley M. (Preventive medicine, 2009)
This study examined utilization and physical activity levels at renovated compared to unrenovated school playgrounds. Ten unrenovated and ten renovated school playgrounds (renovated at least a year prior) in Cleveland, OH were matched on school and neighborhood characteristics. Using direct observation (SOPLAY), the number of persons attending each playground and their physical activity levels were recorded using separate counts for girls, boys, men and women. Each school was observed ten times for 90 min each time outside of school hours in 2005. Paired t-tests, Wilcoxon Signed Ranks tests, and regression analyses were completed to examine differences across school pairs. More persons overall including adults and children utilized the renovated playgrounds compared to the unrenovated playgrounds. The proportion moderately-to-vigorously active was not different between renovated and unrenovated playgrounds although the proportion of children, in particular boys, who were vigorously active was greater at the renovated playgrounds. Although utilization was higher at the renovated playgrounds, absolute utilization was low across all playgrounds. This study suggests that playgrounds renovations may have the potential to increase the number of children utilizing the playground outside of school hours and may increase the proportion of children, especially boys, who are vigorously active.